2007
DOI: 10.1086/522764
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis in a 12-Year-Old HIV-Positive Girl with an Increased Serum Concentration of Efavirenz

Abstract: Clearance and adverse effects of efavirenz are associated with CYP2B6-G516T polymorphism. Little is known about the prevalence of genotypes and implications for screening in children. We report (to our knowledge, for the first time in a child) the emergence of psychosis in a 12-year old white girl with an increased efavirenz concentration and heterozygous gene polymorphism of the CYP2B6-G516T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 11 publications
(12 reference statements)
0
26
1
Order By: Relevance
“…Several studies have confirmed this hypothesis by demonstrating that patients with high plasma concentrations of efavirenz were more likely to experience adverse effects in the central nervous system (Marzolini et al, 2001;Ståhle et al, 2004;Gutiérrez et al, 2005;Hasse et al, 2005;Mathiesen et al, 2006;Lowenhaupt et al, 2007). Consequently, several research groups have studied the relationship between CYP2B6 polymorphisms, the pharmacokinetics of efavirenz, and the appearance of adverse effects in the central nervous system.…”
Section: Oct1mentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have confirmed this hypothesis by demonstrating that patients with high plasma concentrations of efavirenz were more likely to experience adverse effects in the central nervous system (Marzolini et al, 2001;Ståhle et al, 2004;Gutiérrez et al, 2005;Hasse et al, 2005;Mathiesen et al, 2006;Lowenhaupt et al, 2007). Consequently, several research groups have studied the relationship between CYP2B6 polymorphisms, the pharmacokinetics of efavirenz, and the appearance of adverse effects in the central nervous system.…”
Section: Oct1mentioning
confidence: 97%
“…Generally speaking, carriers of the CYP2B6 516T variant, especially those homozygous for the reduced functional allele, seem to have higher plasma concentrations of efavirenz and are much more likely to develop severe neuropsychiatric symptoms (Haas et al, 2004;Hasse et al, 2005;Rotger et al, 2005a;Gatanaga et al, 2007;Lowenhaupt et al, 2007).…”
Section: Oct1mentioning
confidence: 99%
“…The most common mutation observed after efavirenz treatment is K103N, which is also observed with other NNRTIs 3 , Psychiatric symptoms, including insomnia, nightmares, confusion, memory loss, and depression, are common 4 and more serious symptoms such as psychosis may occur in patients with compromised liver or kidney function 5,6 , rash, nausea, dizziness and headache may occur. A general guideline about efavirenz and pregnancy states that efavirenz can cause birth defects and should not be used in women who might become pregnant 7 .…”
Section: Issn: 0975-8232mentioning
confidence: 98%
“…23,25 Patients with a homozygotic 516GϾT substitution show higher efavirenz plasma levels and report more frequent adverse reactions to efavirenz treatment due to less effective intracellular drug clearance compared with those carrying the wild type (GG). These results could not be replicated in one other study.…”
Section: Neuropsychiatric Complications Of Efavirenz Therapymentioning
confidence: 99%
“…These results could not be replicated in one other study. 22 Nevertheless, the findings from Lowenhaupt et al 23 and Rotger et al 25 point to the possibility that previous investigations of efavirenz-related adverse effects may have suffered from low statistical power as they did not take into account inter-individual differences in drug clearance capacity. Drug clearance or efavirenz plasma levels are obvious moderators of any outcome in studies investigating toxicity associated with efavirenz treatment.…”
Section: Neuropsychiatric Complications Of Efavirenz Therapymentioning
confidence: 99%